Sistem Informasi Layanan Tiketing yang Responsif dan Adaptif Berbasis Online - Maulana, Muhammad Fahri; ., Suprianto; Taurusta, Cindy (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The utilization of information technology in the event organizer industry is crucial for enhancing the efficiency and quality of ticketing services. This research explores the implementation of a responsive and adaptive Online Ticketing Service Information System for the FEST Event Organizer. The objective of this study is to improve the system's responsiveness in handling high user volumes and ensuring its adaptability to changing needs in the event industry. Through the implementation of a responsive and adaptive Online Ticketing Service Information System, the aim is to enhance the efficiency of the online ticket sales process, elevate customer satisfaction, and assist the FEST Event Organizer in managing various aspects of their activities more effectively. This research contributes positively to the development of information technology in the field of online ticketing services and can serve as a reference for other event organizers in the industry.